Tankage Failures of Aerobee - Hi and Vanguard Rockets. - Srawley,J E (1956)
The failures of two type 410 stainless steel tankage components of NRL Aerobee-Hi rockets at Fort Churchill, Manitoba, were investigated. One failure is considered to have originated at a section of hand repair to a longitudinal seam weld of the oxidizer (nitric acid) tank. The other failure originated by stress corrosion cracking of the end of the helium pressurizing tank, which is in contact with the nitric acid while stressed almost to its yield strength. The two failures are important, not only in relation to other Aerobee-Hi rockets, but also in relation to Vanguard rockets, which are constructed of the same material and also use nitric acid. A program of stress corrosion testing is being carried out by the manufacturer of the rockets and present indications are that the use of 1/2 to 3/4% anhydrous HF as an inhibitor in the acid will reduce the possibility of stress corrosion failure significantly. Improvements in welding procedures and inspection are being effected by the manufacturer. Additionally, a reduction in operating pressure of the Aerobee-Hi helium tank was agreed upon.